The Influence of Team Assisted Individualazation Method on Metacognitive Ability and Student Achievement in Science Subject at Madrasah Ibtidaiyah Hidayatut Thowalib Pare. - Nurhasanah, Andi (Journal of Islamic Education, 2020)
Metacognitive ability and student learning achievement are two things that needed in the learning process, especially on science subject. By using Team Assisted Individualization Method it can improve metacognitive ability and student learning achievement. This research aims to know about the process of appliying the influence of Team Assisted Individuality (TAI) method on science subject in Madrasah Ibtidaiyah Hidayatut Thowalib Pare. This research uses quantitative research method of quasi experiment control group design. It uses TAI method in experiment class and conventional in control class. After doing the learning process, metacognitive ability is measured by using questionnaires and learning achievement is measured by using pre'test and postest. The results can be seen from the cumulative average of students’ metacognitive ability of 30 students amount 93.3% in the ekserimental class and 85.1% in the cotrol class. The difference between the experimental and control class is 8.2%. While teh average result of student achievement in the experimental class using TAI Method taken from 30 student is 83.16 and the average result of student achievement in the control class is 77.37. this research uses the validity test and the reliabilty of the questionnaire that amount 20 items and followed by 57 repondents both in the experimental class and the control class. The are 30 student repondents in the experimental class and 27 student repondents in the control class that are valid. This data can be seen with significant level = 0.05 and rtable = 0.36. an item is called to be valid when rcount  ≥ rtable. While for the reliabilty of item in the experimental class and in the control class are reliable, with cronbach’s Alpha = 0.731 ≥ 0.70. in this research, normality test distributed normaly because it has asymp. Sign ≥ 0.05 while the result learning of the experimental class has a significant 704 and 432 for the control class. It means that the data is normally distributed.  The experimental class consisting of 30 student respondents has the average 9.333 Tcount 5.234 while Ttable 2.045 with significant level of 0.05 or 5%. Based on the data, it can be counclude that Tcount  ≥ Ttable. It means Ho is rejected and Ha is accpeted. Based on the explanation above, TAI method has an influence on metacognitive ability and student achievement of grade IV on science subjects in MI Hidayatut Thowalib Tegalsari Pare For Academic year 2017-2018.